Species Composition and Dominance of Insect Pests on Cocoa (Theobroma cacao L.) in Mamasa Regency, West Sulawesi - Rosalianti, Alde Lisa; Makerra, Andi Dewi Rizka Ainulia; Amaliah, Rezeki (Center for Ecology, Conservation and Ethnobiology Studies, Universitas Sulawesi Barat, 2026)
Cocoa (Theobroma cacao L.) is one of the most important plantation commodities that contributes significantly to local economic development, particularly in West Sulawesi. However, cocoa productivity often declines due to insect pest attacks. This study aimed to determine the species composition and dominance of insect pests attacking cocoa plants in Rembak Hamlet, Bambang Buda Village, East Rantebulahan District, Mamasa Regency. This research employed a descriptive exploratory method with purposive sampling applied to three cocoa plantation sites, each divided into three subunits measuring 10 m × 5 m. Insect pests were collected using two techniques: direct sampling and soap water traps. The results revealed the presence of ten insect pest species attacking cocoa plants, namely Helopeltis spp., Aulacophora nigripennis, Hyposidra talaca, Planococcus minor, Conopomorpha cramerella, Dolichoderus thoracicus, Adoretus spp., Zeuzera coffeae, Pheidole megacephala, and Camponotus spp. These pests attacked several plant parts, particularly fruits, leaves, and stems, causing various types of damage such as fruit spots, perforated leaves, and stem borings. The analysis indicated that Planococcus minor was the most dominant pest species found on cocoa plants in the study area. The presence of these insect pests may reduce both the quality and quantity of cocoa production. Therefore, appropriate pest management strategies are necessary to support the sustainability of cocoa production in the region